Shelf-Life Prediction of Shredded Duck “Cahyo” by Accelerated Shelf-Life Testing (ASLT) technique Based on The Arrhenius Model - Febrianti, Nadya Dwi Putri; Yulistiani, Ratna; Wicaksono, Luqman Agung; Purnama, Afridho Laksono Indra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Shredded Duck "Cahyo" PT Deltasari Indah Restaurant is a shredded product made from duck meat. The shelf life of Shredded Duck "Cahyo" can be used as an indication in determining the time and expiration date. Expiration information is one of the important information that must be included in each food packaging. examinations made from the repository to changes in quality decline are carried out to decide the shelf life of Shredded Duck "Cahyo". Therefore, a study was conducted to forecast the shelf life of Shredded Duck "Cahyo" PT Deltasari Indah Restaurant. This study's objectives are to decide the critical criteria for determining the shelf life of Shredded Duck "Cahyo" and to forecast the shelf life of Shredded Duck "Cahyo" products stored at different thermal state conditions. In this study, Accelerated Shelf Life Testing utilizing the Arrhenius model was employed. Shredded Duck "Cahyo" packaged in PET jars underwent repository at thermal states of 30?C, 40?C, and 50?C for 28 days, by examinations conducted every 7 days. Key criteria analyzed encompassed water content, Free Fatty Acid (FFA) levels, and total microbial presence. The critical criterion selected was the Free Fatty Acid (FFA) criterion, given its low activation energy (Ea) and high R2 value. outcomes indicated that utilizing the Arrhenius model ASLT approach, the shelf lives of Shredded Duck "Cahyo" at 30?C, 40?C, and 50?C were 58 days, 51 days, and 44 days, respectively. Considering actual repository conditions (20?C and 25?C), the average shelf life of Shredded Duck "Cahyo" was decided to be 65.5 days.